1997
DOI: 10.1002/ejtc.52
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on electronic structures of oxygenated dipoles and mechanisms of ozonolysis reactions

Abstract: SUMMARYThe different orbitals for different spins molecular orbital and complete active space SCF studies of ozone and carbonyl oxide and related ozonolysis reactions were carried out. The RHF, UHF, approximately spin-projected (AP) UHF and CASSCF calculations were performed to elucidate the covalent bond instability of the oxygenated dipoles. The correlation energies were calculated by RMP4, UMP4, APUMP4 and CASPT2 methods. The locations of concerted transition structures for ozonolysis reactions and the full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…To model a rational series of oxidized systems that may occur during the O 3 pulse, we investigate the reactions that can occur between surface A and successive singlet O atoms. Such O atoms may come from the thermal or photolytic dissociation of O 3 or O 2 or from an oxygen plasma, but there are well-known deficiencies in the DFT treatment of these molecules, , so we use singlet O( 1 D) as the reference reactant throughout. In any case, we base our arguments on the relative energies of products, which are unaffected by the choice of reactant.…”
Section: Computationalmentioning
confidence: 99%
“…To model a rational series of oxidized systems that may occur during the O 3 pulse, we investigate the reactions that can occur between surface A and successive singlet O atoms. Such O atoms may come from the thermal or photolytic dissociation of O 3 or O 2 or from an oxygen plasma, but there are well-known deficiencies in the DFT treatment of these molecules, , so we use singlet O( 1 D) as the reference reactant throughout. In any case, we base our arguments on the relative energies of products, which are unaffected by the choice of reactant.…”
Section: Computationalmentioning
confidence: 99%
“…Interaction energies (∆E, eV) between the "frontier" molecular orbitals of nitrilimine and ethene (lowest interaction energies are in boldface type). majority of 1,3-dipolar cycloaddition reactions are believed to proceed via a concerted mechanism (23), although there are now several reports of reactions with a biradical mechanism (1,(61)(62)(63)(64)(65).…”
Section: The Nitrilimine Cycloaddition Mechanismmentioning
confidence: 99%
“…[41][42][43] The significant diradical character of 1,3-dipoles lead to a vigorous debate of concerted versus stepwise mechanisms for 1,3-dipolar cycloadditions. [44][45][46] Early ab initio studies by Goddard, 47 Hiberty, 48 Houk, 49 and others [50][51][52][53] showed that ozone and its concerted TS have a triplet instability at the RHF and MP2 levels of theory. Unrestricted Hartree-Fock theory predicts a stepwise pathway to be favored over the concerted pathway, whereas second-order unrestricted Møller-Plesset perturbation theory (UMP2) computations favor the concerted cycloaddition, with a barrier around 10 kcal mol -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Ozone has a zwitterionic (dipole) all-octet resonance structure and cycloadds at the 1,3 termini with alkenes and alkynes. Typically represented by closed-shell zwitterionic structures, natural orbital occupation and generalized valence bond computations estimate diradical character of ozone to be nearly 33%. The significant diradical character of 1,3-dipoles lead to a vigorous debate of concerted versus stepwise mechanisms for 1,3-dipolar cycloadditions. Early ab initio studies by Goddard, Hiberty, Houk, and others showed that ozone and its concerted TS have a triplet instability at the RHF and MP2 levels of theory. Unrestricted Hartree−Fock theory predicts a stepwise pathway to be favored over the concerted pathway, whereas second-order unrestricted Møller−Plesset perturbation theory (UMP2) computations favor the concerted cycloaddition, with a barrier around 10 kcal mol -1 .…”
Section: Introductionmentioning
confidence: 99%